MEMBANGUN MASYARAKAT SADAR PAJAK DI DESA SIULAK GEDANG - Sumanti, Eva; Yani, Ahmad; Novianto, Wawan; Hutri, Zola Alfan; Miranda, Aprisillia Dea (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
Paying land and building tax (PBB) is one of the obligations of society that meets the criteria. Lack of knowledge and socialization about the importance of paying PBB is one of the obstacles that causes this obligation to be neglected or even ignored. This study aims to describe the tax awareness outreach program for the community in Siulak Gedang village. This socialization was carried out by involving village officials.